2000
DOI: 10.1016/s0741-5214(00)90311-2
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus within an aortic aneurysm does not reduce pressure on the aneurysmal wall

Abstract: We conclude that thrombus within the aneurysm does not reduce both the mean and the pulse pressure near the aneurysmal wall and thus will not reduce the risk of rupture of the aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 19 publications
9
100
5
Order By: Relevance
“…While the earliest models did not include ILT, their incorporation into models of AAAs has developed over the past two decades from axisymmetric [111,112] to 2D eccentric [40] and finally to fully 3D patient-specific geometries [113][114][115][116]. The majority of these computational studies, as well as an in vitro experimental study using a synthetic AAA model with thrombus [117], support the initial work by Inzoli et al [111] that an ILT may provide a mechanically protective effect (i.e., a "cushioning" or "shielding") by reducing the stress on the aneurysmal wall; yet, others question the ability of the porous thrombus to reduce wall stress consistently, as assessed computationally [118] or by direct intraoperative pressure measurements in vivo [119]. Clearly, controversy remains.…”
Section: Implications Of Spatial Distribution-the Shoulder and Neck Rsupporting
confidence: 55%
“…While the earliest models did not include ILT, their incorporation into models of AAAs has developed over the past two decades from axisymmetric [111,112] to 2D eccentric [40] and finally to fully 3D patient-specific geometries [113][114][115][116]. The majority of these computational studies, as well as an in vitro experimental study using a synthetic AAA model with thrombus [117], support the initial work by Inzoli et al [111] that an ILT may provide a mechanically protective effect (i.e., a "cushioning" or "shielding") by reducing the stress on the aneurysmal wall; yet, others question the ability of the porous thrombus to reduce wall stress consistently, as assessed computationally [118] or by direct intraoperative pressure measurements in vivo [119]. Clearly, controversy remains.…”
Section: Implications Of Spatial Distribution-the Shoulder and Neck Rsupporting
confidence: 55%
“…Xenos et al showed an uneven pressure distribution in the case of a type I endoleak [22], Pacanowski et al detected a higher pressure close to the stent graft compared to the one close to the aneurysm wall [23], which might be dependent upon the microstructure of the thrombus [24]. In contrast, Dias et al and Schurink et al found an almost even distribution inside the thrombus [7,25]. We are aware that in our model the thrombus represents a gelatinous, non-wall-adhesive state of the organisation process and is not comparable to organised thrombi after 6 months [26].…”
Section: Discussionmentioning
confidence: 98%
“…The mechanical role of the ILT on AAA wall stress distributions is controversial. Early experimental studies 15,59 suggest that the presence of ILT does not reduce the pressure acting on the aneurysmal wall. However, early computational studies 14,34,48 based on both simplified material models and idealized AAA geometry suggest that the ILT reduces the wall stress level.…”
Section: Computational Analysismentioning
confidence: 99%
“…At least of similar importance, Schurink et al 59 substantiated that a thrombus within an aneurysm does not reduce both the mean and the pulse pressure near the aneurysm wall, and thus would not reduce the risk of AAA rupture from the loading point of view. The role of ILT within the structural stability of AAA, specifically in relation to the risk of rupture, is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%